Effect of laser shock peening on the microstructure and wear resistance of CoNiCrAlY coatings - Jiyuan Huang; Junming Luo; Jiling Xu; Jun Huang (Journal of Materials Research and Technology)
Ti6Al4V alloy (TC4), characterized by its low density, excellent toughness, and strong weldability, is widely applied in the aerospace field. However, it suffers from low hardness and poor wear resistance, which are significantly reduced under high-temperature working conditions. In this study, a CoNiCrAlY coating was produced by atmospheric plasma spraying (APS), with subsequent strengthening of the coating surface through laser shock peening (LSP). The results demonstrate that the number of the pores on the surface of the coating is reduced after LSP treatment, resulting in enhancements in both hardness and adhesion. At room temperature, the wear rate of the LSP treated coating is reduced by 13.74% compared to that of the untreated coating. Under elevated temperature conditions, a glaze layer is formed during the friction and wear process, preventing direct contact between the friction pairs, thus enhancing the wear resistance of the coating. The CoNiCrAlY coating applied to the surface of TC4 exhibits optimal wear resistance at 500 °C, and the wear rate of the LSP treated coating is further diminished.